Flower margins support natural enemies adjacent to apple orchards but evidence of spill-over is mixed - Howard, Charlotte; Fountain, Michelle T.; Brittain, Claire; Burgess, Paul J.; Garratt, Michael P. D. (Elsevier, 2025)
Perennial flower margins next to apple orchards can reduce the spread of aphid pests on apple trees and reduce the percentage of trees with fruit damage. To explore the mechanism behind this, we compared the vegetation community in three orchard habitats (flower margins, headlands, and alleyways) to determine whether the presence of a flower margin changed the diversity, abundance, and community of natural enemies of rosy apple aphid (Dysaphis plantaginea) in orchard ground vegetation and apple trees. Despite no evident spill-over of plant species into orchards, there was an increased Shannon diversity of natural enemies in the ground vegetation of flower margin orchards compared with controls. This suggests spill-over of natural enemies from the flower margins can reach up to 50 m from the orchard edge. However, we did not find evidence of broad differences between natural enemy taxa abundance, diversity, or community structure on the apple trees themselves. The mechanism behind improved pest control by flower margins is unclear but could be linked to the mobility of certain natural enemy groups or mutualistic relationships with ants. A better understanding of this mechanism would help to optimise the use of flower margins for sustainable pest suppression.
Data available from the University of Reading Research Data Archive
Keywords: 4103 Environmental Biotechnology; 41 Environmental Sciences; Agronomy & Agriculture; 30 Agricultural, veterinary and food sciences; 44 Human society